Firearm Legislation and Firearm Mortality in the USA: A Cross-Sectional State-Level Study. Issue 9 (September 2016) - Kalesan, Bindu; Mobily, Matthew E.; Keiser, Olivia; Fagan, Jeffrey A.; Galea, Sandro
Abstract : (Abstracted from Lancet 2016;387:1847–1855) Firearm violence and firearm mortality are a cause for concern in the USA. Several laws, including the Brady Law, child-access prevention laws, and stand-your-ground laws have been enacted in different states to address gun violence.